Irreversible acute kidney injury following efavirenz/tenofovir disoproxil fumarate/emtricitabine overdose - Ensor, Jason; Malaka, Shumani; Barton, Benita; Black, John; Freercks, Robert (African Journal of Nephrology, 2018)
Nephrotoxicity due to chronic use of tenofovir disoproxil fumarate (TDF) is well described, but very little is known or published about the effects of acute toxicity or the clinical management of this condition. We present here a case of acute and irreversible renal failure that followed an intentional overdose of fixed dose combination antiretroviral therapy containing efavirenz, TDF and emtricitabine. The renal histology findings are discussed and a rationale for the use of emergency haemodialysis in the management of TDF overdose is presented.